Integrated system of multiple batches to evaluate the continuous performance of microbial cells in decolourization processes - Vatandoostarani, Simin; Lotfabad, Tayebe Bagheri; Heidarinasab, Amir; Ebadipour, Negisa; Yaghmaei, Soheila (Journal of Environmental Chemical Engineering, 2018)
[Display omitted] •Establishing an expanded immobilized microbial bed (EIMB) reactor.•Alginate capsulated S. cerevisiae ATCC 9763 was employed for decolourization study.•Reactor was run in an innovative approach, integrated system of five batches (ISFB).•ISFB set-up was utilized to investigate the long-term use of microbial cells.•ISFB is an easy approach for bench-scale studies on continuous microbial performance. Azo dye degradation in wastewater treatment is a subject which has garnered the attention of many research studies. In this study, an innovative approach, namely, an integrated system of five batches (ISFB), was developed to investigate the capability of Saccharomyces cerevisiae ATCC 9763 for continuous degradation of methyl red as a representative azo dye. Toward this end, an expanded immobilized microbial bed (EIMB) reactor was established with a bed of encapsulated yeast cells in sodium alginate. EIMB reactor was run in two modes, single batch and ISFB. Moreover, durability of the microbial cells was evaluated by repeating the continuous decolourization eight sequential times in EIMB at ISFB mode with the same cells. ISFB set-up can simulate a continuous process while avoiding the complexity of utilizing continuous reactors. Spectrophotometry results show that 6 ± 0.17 h was required for complete decolourization in EIMB reactor at single batch mode which estimates a decolourization rate (RDec) of 8.9 ± 0.3 g h−1in this set-up. Subsequently, decolourization rate incrementally increased ≃2.8 times while ISFB mode was applied to the EIMB system and this rate was approximately maintained during eight consecutive runs. The changes in morphology and bioavailability of the immobilized S. cerevisiae were monitored through scanning electron microscopy.